Early Spironolactone Treatment Attenuates Heart Failure Development by Improving Myocardial Function and Reducing Fibrosis in Spontaneously Hypertensive Rats - Cezar, Marcelo D.M. [UNESP]; Damatto, Ricardo L. [UNESP]; Pagan, Luana U. [UNESP]; Lima, Aline R.R. [UNESP]; Martinez, Paula F.; Bonomo, Camila [UNESP]; Rosa, Camila M. [UNESP]; Campos, Dijon H.S. [UNESP]; Cicogna, Antonio C. [UNESP]; Gomes, Mariana J. [UNESP]; Oliveira, Silvio A.; Blotta, Daniella A. [UNESP]; et al. (Karger Publishers, 2015)
Background: We evaluated the role of the aldosterone blocker spironolactone in attenuating long-term pressure overload-induced cardiac remodeling and heart failure (HF) in spontaneously hypertensive rats (SHR). Methods and Results: Thirteen month-old male SHR were assigned to control (SHR-C, n=20) or spironolactone (SHR-SPR, 20 mg/kg/day, n=24) groups for six months. Normotensive Wistar-Kyoto rats (WKY, n=15) were used as controls. Systolic blood pressure was higher in SHR groups and unchanged by spironolactone. Right ventricular hypertrophy, which characterizes HF in SHR, was less frequent in SHR-SPR than SHR-C. Echocardiographic parameters did not differ between SHR groups. Myocardial function was improved in SHR-SPR compared to SHR-C [developed tension: WKY 4.85±0.68; SHR-C 5.22±1.64; SHR-SPR 6.80±1.49 g/mm2; -dT/dt: WKY 18.0 (16.0-19.0); SHR-C 20.8 (18.4-25.1); SHR-SPR 28.9 (24.2-34.6) g/mm2/s]. Cardiomyocyte cross-sectional area and total collagen concentration (WKY 1.06±0.34; SHR-C 1.85±0.63; SHR-SPR 1.28±0.39 μg/mg wet tissue) were greater in SHR-C than WKY and SHR-SPR. Type 3 collagen expression was lower in SHR-C than WKY and unchanged by spironolactone. Soluble collagen, type I collagen, and lysyl oxidase did not differ between groups. Conclusion: Early spironolactone treatment decreases heart failure development frequency by improving myocardial systolic and diastolic function and attenuating hypertrophy and fibrosis in spontaneously hypertensive rats.
Keywords: Aldosterone antagonist; Cardiac remodeling; Collagen; Papillary muscle; Spontaneously hypertensive rat; Ventricular function